2013
DOI: 10.3171/2013.7.jns122128
|View full text |Cite
|
Sign up to set email alerts
|

Risk of very early recurrent cerebrovascular events in symptomatic carotid artery stenosis

Abstract: Object The risk of recurrence of cerebrovascular events within the first 72 hours of admission in patients hospitalized with symptomatic carotid artery (CA) stenoses and the risks and benefits of emergency CA intervention within the first hours after the onset of symptoms are not well known. Therefore, the authors aimed to assess 1) the ipsilateral recurrence rate within 72 hours of admission, in the period from 72 hours to 7 days, and after 7 days in patients presenting with nondisabling stroke, transient isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Few authors describing early CEA have provided information allowing comparative analysis with their own previous delayed CEA experience (table VI). However, some authors [35][36][37]40,42 have recently reported that early CEA within 2 weeks in comparison with a delayed surgery was not associated with higher perioperative stroke and death risk, thus supporting our findings. In her study describing very early CEA, i.e., within 2 days, Stromberg et al 34 showed an impressive 30-day stroke and death rate of 11.5% but this observation was not confirmed by the most recent publications [35][36][37][38] in which 30-day stroke and death rate range from 2.4% to 4.5%.…”
Section: Discussionsupporting
confidence: 91%
“…Few authors describing early CEA have provided information allowing comparative analysis with their own previous delayed CEA experience (table VI). However, some authors [35][36][37]40,42 have recently reported that early CEA within 2 weeks in comparison with a delayed surgery was not associated with higher perioperative stroke and death risk, thus supporting our findings. In her study describing very early CEA, i.e., within 2 days, Stromberg et al 34 showed an impressive 30-day stroke and death rate of 11.5% but this observation was not confirmed by the most recent publications [35][36][37][38] in which 30-day stroke and death rate range from 2.4% to 4.5%.…”
Section: Discussionsupporting
confidence: 91%
“…In a similar series, where patients were seen about 14 days after symptom onset, Kastrup observed that over the next 7 days, 3% suffered a recurrent TIA, while 12% developed new DWI lesions on MRI [79]. In Mono's series, where 94 patients were admitted within 48 h of onset of symptoms and where CEA was performed a median of 5 days after onset of symptoms, 13% suffered in patient recurrent neurological events before undergoing CEA [15]. The highest rates of recurrent stroke (prior to expedited CEA) were reported by Johansson, who found that the rate of recurrent ipsilateral stroke was 5% at 48 h after onset of symptoms, increasing to 8% at 7 days and 11% at 14 days [12].…”
Section: How Soon After Thrombolysis Should Cea (Cas) Be Performed?mentioning
confidence: 91%
“…Johansson (2013) 5% 8% 11% [12] Mono (2013) 4% [15] Merwick (2013) 8% [17] Marnane ( Salem et al have also reported that ultrasound markers of carotid plaque instability (in this case a large lipid core and a Gray Scale Median <25) were highly predictive of a significantly increased risk of recurrent neurological events in the 48-72-h period prior to expedited CEA [22]. In a subsequent study, two ultrasound-based plaque features were associated with a high probability of there being a histologically unstable carotid plaque: i) plaque area >95 mm 2 and ii) a juxta-luminal black area >6 mm 2 .…”
mentioning
confidence: 98%
“…However, t he q uestion o f the optimal t iming of intervention in the individual case of symptomatic carotid artery remains to be answered [70].…”
Section: The Issue Of Stroke Recurrencementioning
confidence: 99%